2016
DOI: 10.1093/omcr/omw016
|View full text |Cite
|
Sign up to set email alerts
|

A global amnesia associated with the specific variant of posterior reversible encephalopathy syndrome (PRES) that developed due to severe preeclampsia and malignant hypertension

Abstract: A case is reported of a 26-year-old primiparous woman in the 32nd week of gestation who presented to the emergency department with the symptoms of a severe headache, nausea and vomiting. The patient was diagnosed with preeclampsia that later progressed to eclampsia. This state was characterized by a sudden onset of a headache and diplopia that advanced to cortical blindness and precipitated significant alterations in mental status, most notable being global amnesia that resolved within 48 h. A post-partum magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…On subsequent postpartum fluid-attenuated inversion recovery (FLAIR) coronal magnetic resonance imaging (MRI), vasogenic edema in the occipital cortex was found to be the main cause of the cortical blindness. The patient eventually fully recovered with no edematous lesions visible on the 6 months follow-up MRI scan (Borovac et al, 2016). Two other case studies reported transient cortical blindness presentation during the antepartum and postpartum period.…”
Section: Visual Changes Have Been Reported In Preeclampsia Patientsmentioning
confidence: 72%
See 2 more Smart Citations
“…On subsequent postpartum fluid-attenuated inversion recovery (FLAIR) coronal magnetic resonance imaging (MRI), vasogenic edema in the occipital cortex was found to be the main cause of the cortical blindness. The patient eventually fully recovered with no edematous lesions visible on the 6 months follow-up MRI scan (Borovac et al, 2016). Two other case studies reported transient cortical blindness presentation during the antepartum and postpartum period.…”
Section: Visual Changes Have Been Reported In Preeclampsia Patientsmentioning
confidence: 72%
“…Headache and visual changes are two of the most common preceding symptoms to a (pre)eclampsia episode. Multiple case studies over the past 20 years have reported visual changes in (pre)eclampsia patients during the antepartum and postpartum period (Kesler et al, 1998;Garg et al, 2013;Bereczki et al, 2016;Borovac et al, 2016). Headaches during the peripartum and postpartum period, when associated with elevated blood pressure, tend to reflect an elevation in cerebellar perfusion pressure, cerebral edema, and encephalopathy (Gestational Hypertension and Preeclampsia, 2020).…”
Section: Visual Changes Have Been Reported In Preeclampsia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preexistent essential 111 or new-onset malignant 112 hypertensions are commonly described in the setting of PRES, leading a variety of authors to utilize hydrostatic endothelial injury in models designed to explain the pathogenesis of this condition. 14,34,45,50,51,58,104,109,[113][114][115][116][117][118][119] Sudden elevations of the arterial pressure exceeding the upper limits of cerebrovascular autoregulation forces diffuse dilatation of the cerebral vasculature at the arteriolar level, presenting high perfusion pressures to the microcirculatory capillaries, thus mechanically compromising the endothelial tight junctions, enhancing the blood-brain barrier permeability, and generating vasogenic edema of the cerebral parenchyma.…”
Section: Hypertensionmentioning
confidence: 99%
“…Preexistent essential 111 or new-onset malignant 112 hypertensions are commonly described in the setting of PRES, leading a variety of authors to utilize hydrostatic endothelial 14,34,45,50,51,58,104,109,[113][114][115][116][117][118][119] Sudden elevations of the arterial pressure exceeding the upper limits of cerebrovascular autoregulation forces diffuse dilatation of the cerebral vasculature at the arteriolar level, presenting high perfusion pressures to the microcirculatory capillaries, thus mechanically compromising the endothelial tight junctions, enhancing the blood-brain barrier permeability, and generating vasogenic edema of the cerebral parenchyma. 14,58,115 Although Mueller-Mang et al 120 demonstrated that the extent and pattern of vasogenic cerebral edema in patients with PRES were risk factor invariant, Karakis et al demonstrated that a mild degree of hypertension typically generates vasogenic edema predominantly affecting the supratentorial white matter, in contrast with severe degrees of hypertension, shown to preferentially cause vasogenic edema extending to the deep gray nuclei and cerebellar and rhombencephalic contents of the infratentorial compartment.…”
Section: Hypertensionmentioning
confidence: 99%